Literacy Festival Program as a Means of Ecology Education for Society - Mulyono, Dinno; Hufad, Ahmad; Wahyudin, Uyu (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Literacy is one of the supporting concepts for development, including community empowerment. The approach is forming a literacy community that regularly holds literacy festivals. With literacy, society is expected to understand its role in development. The theories used in this study were the concepts of literacy and ecological education. This study applied a descriptive qualitative approach using interviews, observations, and documentation studies. The main reason for choosing the research method was to understand the existing phenomena in-depth and completely, especially in the program implemented by the Bening Saguling Foundation. This study showed that community empowerment developed using a dialogic approach had positive implications for developing the community's ecological and economic awareness. This study concluded that the social literacy approach could develop public awareness of various potentials to direct society to establish economic independence.